Relationship between Physical Function and Sleep Quality in African Americans - Thorpe, Roland J. (J Clin Sleep Med, 2016)
STUDY OBJECTIVES: There is a growing body of research examining the relationship between sleep and functional outcomes. However, little is known about sleep and physical functioning in older African Americans. METHODS: Data for this project included 450 community-dwelling older African Americans (71.4 ± 9.2 years of age) who participated in the Baltimore Study of Black Aging. Overall sleep pattern and quality was measured by the Pittsburgh Sleep Quality Index (PSQI). Physical functioning was measured by the number of activities of daily living that each participant reported difficulty (ADL; e.g. eating, dressing, and bathing). Negative binomial regression models were conducted to estimate the association between sleep quality and physical functioning. RESULTS: Seventy-two percent of the participants reported poor sleep quality. African Americans who reported poor sleep quality had a greater likelihood of an increase in the number of difficulties in ADLs that they reported even after accounting for demographic characteristics and health conditions. The relationship between sleep quality and physical functioning did not vary by gender. CONCLUSIONS: Sleep may be an important factor to consider when seeking to improve physical functioning among community-dwelling older African Americans. CITATION: Thorpe Jr RJ, Gamaldo AA, Salas RE, Gamaldo CE, Whitfield KE. Relationship between physical function and sleep quality in African Americans. J Clin Sleep Med 2016;12(10):1323–1329.